Identification of Herpesviridae in Macaca Fascicularis Using the Nested PCR Method at PSSP IPB - Malik, Abdul; Sulistiawati, Erni; Yuliana; Saepuloh, Uus (IPB University, 2025)
PCR technique is used to detect the presence of Herpesviridae viruses in Macaca fascicularis that exhibit no clinical symptoms and identify them using nucleotide base sequences. This study aimed to detect and identify the presence of nucleotide base sequences in the Herpesviridae virus family in Macaca fascicularis at PSSP IPB. The study utilized 20 nasal swab samples from Macaca fascicularis. Extraction of DNA utilizing the QiaAmp™ DNA mini kit and subsequent measurement of DNA concentration. Amplification of target DNA utilizing the nested PCR technique. Sample with positive results from electrophoresis were sequenced to obtain nucleotide sequences. The average measurement value of DNA extraction concentration was 25.07 ng/µl. The DNA purity ratios at wavelengths A260/A280 and A260/A230 averaged 1.95 and 0.27, respectively. The electrophoresis results indicated a band size of 215 bp in sample code 01, corresponding to the positive control band. The sequencing results were analyzed using BLASTn on the NCBI site, revealing similarity with Macaca fascicularis lymphocryptovirus. The BLAST sample results demonstrated a Query Cover value of 100% and a percentage of identity of 98.84%.